Ultrasoundapplication in isomaltulose impregnation followed by convective drying in apple slices - Souza, Amanda Umbelina de (2021)
Isomaltulose, also known as palatinose, is a functional carbohydrate that has properties such as slow digestion, low glycemic index, and prolonged release of energy. It is marketed as a powder and has been commonly added to beverages used by sportsmen and diabetics. Its incorporation in dried fruit could be a practical alternative for its consumption. The present work aimed to use the double stage technique (D3S) for isomaltulose incorporation and drying of apple slices. The D3S stage prioritized a condition leading mainly to isomaltulose incorporation and water loss. In the first stage of the D3S process, native sugars were partially removed from the fruit. In the second, isomaltulose was incorporated into the fruit. Both processes took place at 25 and 35 °C. The influence of the use of ultrasound was also tested. The incorporation of isomaltulose was measured by the gain of solids. Other parameters like water loss, related to fruit dehydration, water activity (aw), soluble solids content (°Brix), color parameters and volumetric shrinkage were also evaluated. After D3S, drying was performed in a tunnel dryer at 50 and 70 °C and air velocity of 1.5 m/s until the moisture content of 0.12 ± 0.01 kg H2O/kg dry matter. The effect of D3S pre-treatment on the final product was evaluated for the moisture content, aw, total phenolic content, antioxidant activity, shrinkage and color parameters. The process that promoted the highest isomaltulose incorporation and water loss consisted of immersion for 25 min in the first stage and ultrasound-assisted impregnation for 40 min in the second stage. A reduction in aw, change in color parameters, and decrease in shrinkage were observed in this condition. However, the drying time increased and there were significant losses in total phenolic compounds, reduction in antioxidant activity and rehydration capacity. In addition, a greater color difference was observed compared to the untreated samples. In summary, the D3S process followed by drying provided an incorporated isomaltulose product, but with altered nutritional and physical properties.